Estrogens are neuroprotective factors for hypertensive encephalopathy - Pietranera, Luciana (2015)
Estrogens are neuroprotective factors for brain diseases, including hypertensive encephalopathy. In particular, the hippocampus is highly damaged by high blood pressure, with several hippocampus functions being altered in humans and animal models of hypertension. Working with a genetic model of primary hypertension, the spontaneously hypertensive rat (SHR), we have shown that SHR present decreased dentate gyrus neurogenesis, astrogliosis, low expression of brain derived neurotrophic factor (BDNF), decreased number of neurons in the hilus of the dentate gyrus, increased basal levels of the estrogen-synthesizing enzyme aromatase, and atrophic dendritic arbor with low spine density in the CA1 region compared to normotensive Wistar Kyoto (WKY) ratsl. Changes also occur in the hypothalamus of SHR, with increased expression of the hypertensinogenic peptide arginine vasopressin (AVP) and its V1b receptor. Following chronic estradiol treatment, SHR show decreased blood pressure, enhanced hippocampus neurogenesis, decreased the reactive astrogliosis, increased BDNF mRNA and protein expression in the dentate gyrus, increased neuronal number in the hilus of the dentate gyrus, further increased the hyperexpression of aromatase and replaced spine number with remodeling of the dendritic arbor of the CA1 region. We have detected by qPCR the estradiol receptors ERα and ERβ in hippocampus from both SHR and WKY rats, suggesting direct effects of estradiol on brain cells. We hypothesize that a combination of exogenously given estrogens plus those locally synthesized by estradiol-stimulated aromatase may better alleviate the hippocampal and hypothalamic encephalopathy of SHR. This article is part of a Special Issue entitled "Sex steroids and brain disorders",